Pengaruh Financial Knowledge, Financial Attitude, dan Locus of Control terhadap Personal Financial Management Behavior pada Mahasiswa S1 Program Studi Manajemen di Universitas Primagraha Angkatan 2021 - Adzroo A’adilah Wijayati; Febri Hayati; Riki Gana Suyatna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to investigate and analyze the influence of financial knowledge, financial attitude and locus of control variables on personal financial management behavior of undergraduate students in the Management Study Program at Primagraha University class of 2021. This research applies a quantitative approach using primary data with a non-probability sampling method using purposive techniques sampling.. Data collection technique by distributing questionnaires to 50 undergraduate students of the Management Study Program at Primagraha University class of 2021. The test results show that financial knowledge towards personal financial management behavior shows a calculated t value = -4.683 and a sig probability value of 0,000. The financial attitude variable towards personal financial management behavior shows a t value = 8.956 and a sig probability value of 0,000. And the locus of control variable on personal financial management behavior shows a t value = 3.180 and a sig probability value of 0,003. The results of this research partially show that the variables financial knowledge, financial attitude, and locus of control have a significant influence on personal financial management behavior.